IMPLEMENTASI KEBIJAKAN PENGELOLAAN LINGKUNGAN HIDUP TERHADAP AKTIVITAS INDUSTRI DI KOTA SEMARANG (Studi Implementasi PERDA No.13 Tahun 2006 Tentang Pengelolaan Lingkungan Hidup) - Mirfani Wulanda Putri; Rina Martini; Purwoko . (Journal of Politic and Government Studies, 2016)
AbstractEnvironment and natural resources is a gift from God Almighty shall bepreserved and developed ability to remain can be the source and support of humanlife and other living for survival. This study aims to determine how theimplementation of environmentalmanagement policies in industrial activity in thecity of Semarang according to local regulations Semarang City Number 13 Year2006 regarding environmental control and to determine the obstacles or barriersanything that happens in the implementation of environmental managementpolicies in industrial activity in Semarang city.This study took place in Semarang city government, because of the variousproblems that arise on the management, protection and environmental pollutiondue to the many industry sectors, as well as the community's role in it, often havea variety of interesting new problems to be studied further.The results showed that the implementation of Regulation mayor ofSemarang No. 5 of 2009 concerning Directive Implementing Regulation of theSemarang City Number 13 Year 2006 regarding Environmental Control has beenperforming well, having been through the process of delivering a regulation withthe right target, and then implementing these regulations in accordance with theduties principal and functions of the actors who play a direct role to implement aregulation. Impacts of air pollution motor vehicle can be prevented by theseelections is enough traffic away from population areas and reduce trafficcongestion. While the factors that inhibit failure of the community in thedevelopment and maintenance of the environment, internal constraints inhibitingthe realization of development. The progress of industry had a positive impactwheels society, but in reality progress industry not only had an impact on theinterconnected economy, but also the environment in which the companyoperates.Keywords: Activities Industry, Environment